Pemanfaatan Probiotik Guna Peningkatan Kualitas Telur Puyuh - Kalsum, Umi; Rahardjo, Liliek; Wadjdi, Muhammad Farid (Jurnal Riset Agribisnis dan Peternakan, 2016)
This study was conducted to ascertain the effect of adding probiotics to feed on the quality of quail’s eggs. Lactobacillus salivarius encapsulation (Ls encaps) was used as a  probiotic. A randomized block design was used to assign four levels of Ls endcaps administration, that is P0 = Standard feed without Ls endcaps, P1 = P0 + 107 cells/g Ls endcaps, P2 = P0 + 108 cells/g  Ls endcaps and P3 = P0 + 109 cells/g Ls endcaps. The results showed that adding Ls encaps did not alter significant egg quality (egg weight, the level protein of an egg, and eggshell) but it significantly lowered cholesterol content in egg. In conclusion, L. Salivarius encaps may be used as a feed additive in quail diets to reduce egg cholesterol content.43.85 %, respectively. In conclusion, Ls endcaps may be used as a feed additive for quail to enhance egg quality leading to improve our health.